2002
DOI: 10.1215/03616878-27-5-731
|View full text |Cite
|
Sign up to set email alerts
|

Policy Feedback and Public Opinion: The Role of Employer Responsibility in Social Policy

Abstract: This study extends the literature on policy feedback and explores the extent to which public attitudes reflect learning from past government initiatives. We analyze the ways in which feedback mechanisms affecting public attitudes may differ from those earlier identified in the literature. We apply this general analytic framework to help explain variation in public attitudes toward private employer involvement in health care, explore possible causal pathways, and offer some preliminary empirical tests of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
0
38
0
1
Order By: Relevance
“…Panel survey data of attitudes toward gays and lesbians found that respondents in states with popular votes to ban same-sex marriage had more negative attitudes toward gays and lesbians after the policy was passed than before (Donovan and Tolbert 2013). Gusmano, Schlesinger, and Thomas (2002) identify three possible mechanisms for policy feedback: exposure, experience, and signaling. Exposure is defined as "the longer citizens interact with a particular policy or institution, the more 'comfortable' they become" (Gusmano, Schlesinger, and Thomas 2002, 735).…”
Section: Policy Feedbackmentioning
confidence: 90%
“…Panel survey data of attitudes toward gays and lesbians found that respondents in states with popular votes to ban same-sex marriage had more negative attitudes toward gays and lesbians after the policy was passed than before (Donovan and Tolbert 2013). Gusmano, Schlesinger, and Thomas (2002) identify three possible mechanisms for policy feedback: exposure, experience, and signaling. Exposure is defined as "the longer citizens interact with a particular policy or institution, the more 'comfortable' they become" (Gusmano, Schlesinger, and Thomas 2002, 735).…”
Section: Policy Feedbackmentioning
confidence: 90%
“…The problems of the uninsured are easier to neglect when citizens and policy makers endorse competing images of access to health care as a societal right, a community responsibility, a perk of a good job, a professional obligation, or a market commodity (55,63,161,163,181).…”
Section: Locus Of Responsibilitymentioning
confidence: 99%
“…Once enacted, policies can affect a variety of different actors. Studies in the policy feedback literature often focus on elites and organized interests (Hacker, ; Karch, ; Skocpol, ) or mass public opinion (Gusmano, Schlesinger, & Thomas, ; Hetling, McDermott, & Mapps, ; Soss & Schram, ; Wlezien, ). While previous research demonstrates the macro‐level effects of public policies, I am interested in the effects of these programs on program participants.…”
Section: Policy Feedback and Political Learningmentioning
confidence: 99%